Comparative analysis of neuroinflammatory pathways in Alzheimer’s disease, Parkinson’s disease, and multiple sclerosis: insights into similarities and distinctions - Doroszkiewicz, Julia; Winkel, Izabela; Mroczko, Barbara (Frontiers in Neuroscience, 2025)
Neurodegenerative diseases, contributing to the significant socioeconomic burden due to aging society, are gaining increasing interest. Despite each disease having different etiologies, neuroinflammation is believed to play a crucial role in Alzheimer’s disease (AD), Parkinson’s disease (PD), and multiple sclerosis (MS). In addition to the pathogenic function of inflammation in the brain there is growing evidence that immune responses are essential for neuroregeneration. This review compares and contrasts the neuroinflammatory pathways that selected neurodegenerative diseases share and have in common. In AD, tau tangles and beta-amyloid plaques cause microglia and astrocytes to become activated in an inflammatory response. Alpha-synuclein aggregation stimulate neuroinflammation in Parkinson’s disease, especially in the substantia nigra. In Multiple Sclerosis an autoimmune attack on myelin is connected to inflammation via invading immune cells. Commonalities include the release of pro-inflammatory mediators like cytokines and activation of signaling pathways such as NF-κB and MAPK. Comprehending these common routes is essential for discovering early diagnostic possibilities for the diseases and possible tailored treatments. Our work underscores the potential for insights into disease mechanisms. Identifying common targets offers promise for advancing our understanding and potential future treatment approaches across these debilitating disorders.